A relationship between body size and the gut microbiome suggests a conservation strategy - Tong Xin; Qian Ye; Dini Hu (Microbiology Spectrum, 2025)
ABSTRACT A key goal of conservation is to protect the biodiversity of wild species to support their continued evolution and survival. Conservation practice has long been guided by genetic, ecological, and demographic indicators of risk. Cope’s rule suggests that species tend to evolve larger body sizes over time. Here, we provide strong evidence to support the inclusion of body size when formulating wildlife conservation strategies. The gut microbiome can mirror the physiological and environmental adaptation status of the host. This study established a connection between body size and the gut microbiome in the Felidae family using 70 fecal samples collected from 18 individuals through metagenomic data analysis and mining metagenome-assembled genomes (MAGs). Two enterotypes were identified in the Felidae gut: Bacteroides and Clostridium. Medium-sized felids predominantly harbored Clostridium, associated with pathogenicity, whereas large and small felids harbored both beneficial Bacteroides and pathogenic Clostridium. Species that evolved larger body sizes over time exhibited distinct changes in gut microbial communities, such as enhanced nutrient extraction and metabolic capabilities. Larger felids exhibited a more diverse, stable gut microbiome engaged in metabolic processes and extensive host interactions, indicating an evolved functional role in various biological processes. Conversely, that of smaller felids is less diverse, with more viruses and pathogenic elements primarily involved in chemical synthesis. These findings provide essential insights for developing conservation strategies that consider the nutritional needs of different-sized feline species, control the transmission of pathogens, and allocate resources based on their unique gut microbiome characteristics.IMPORTANCEBody size is a fundamental trait that varies greatly among taxa and has important implications for life history and ecology. Cope’s rule suggests that species tend to evolve larger body sizes over time. However, its correlation to body size evolution remains unclear. This study aimed to establish a connection between body size and the gut microbiome in the Felidae family through metagenomic data analysis. Our results support Cope’s rule, illustrating that increased body size correlates with shifts in the gut microbiome, enhancing survival and adaptability.